Migraine Successfully Treated with a Milk-Gluten-Sugar-Free Diet: A Case Report - Joz?lio Freire de Carvalho; Maria Betania Torales; Laiane Paula Silva Santos; Rosangela Passos de Jesus (Integrative Medicine Reports, 2022)
Objective: To describe a patient's clinical case with migraine who improved with a milk-gluten-sugar-free diet. Clinical Features: A patient with migraine for 25 years has had episodic pain 1?2 days long, in addition to photophobia and phonophobia. She was treated with analgesics, topiramate, and antidepressants, with no improvement in her condition. Intervention and outcome: She was treated with a milk-gluten-sugar-free diet and improved in about 3 weeks. Conclusion: This is a case report of a patient with migraine treated with a milk-gluten-sugar-free diet who had a remarkable clinical response.